The Effect of E-Wallet Usage on Personal Cash Flow and Net Worth Ratio in Generation Z - Nur Safitri, Wanda; Fadali, Fadali Rahman; Zuhal, Zuhal Thoriq; Aisyah , Aisyah Rievliani; Isnain , Isnain Bustaram (Yayasan Kita Menulis, 2026)
The rapid development of financial technology has significantly transformed individual digital financial behavior, particularly through the increasing use of electronic wallets (e-wallets) among Generation Z. As digital natives, this generation is highly exposed to online transactions, yet their financial management capabilities remain varied. This study aims to analyze the effect of e-wallet usage on personal financial stability, specifically measured through personal cash flow and net worth ratio. Additionally, technological adaptation patterns within modern student financial activities significantly increase complexity, influencing how digital tools are utilized. A quantitative survey method was employed, involving 30 respondents who are active e-wallet users and university students in Pamekasan, Madura. Data were collected through a structured questionnaire and tested for reliability, yielding a Cronbach’s Alpha value of 0.761, indicating acceptable internal consistency. The Kolmogorov–Smirnov normality test showed that some variables met the normal distribution criteria. Results of multiple linear regression revealed that the intensity of e-wallet use, perceived usefulness, and perceived financial impact did not have a significant effect on cash flow, with a significance value greater than 0.05. The model’s R Square value of 0.087 further suggests that only 8.7% of changes in cash flow can be explained by the examined variables, while the remaining 91.3% is influenced by factors such as income level, spending behavior, and financial literacy. These findings indicate that although e-wallets have become an integral part of students’ daily transactions, their impact on overall financial stability remains limited. Strengthening digital financial literacy is recommended to promote wiser and more responsible e-wallet usage.